2017
DOI: 10.5489/cuaj.4208
|View full text |Cite
|
Sign up to set email alerts
|

Radical cystectomy in patients with disseminated disease: An assessment of perioperative outcomes using the National Surgical Quality Improvement Program database

Abstract: Introduction: We sought to determine the effect of the presence of disseminated disease on perioperative outcomes following radical cystectomy for bladder cancer. Methods: We identified 4108 eligible patients who underwent radical cystectomy for bladder cancer using the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) database. We matched patients with disseminated cancer at the time of surgery to those without disseminated cancer using propensity scores. The primary outcome o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In our current review, the data from three studies that followed up the patients for three months after cystectomy revealed that VTE rates were still high; this may be due to patients having further treatment and hospitalisation [15,18,50]. According to the study by , the VTE rate peaks at 20 days after cystectomy in BC patients; however, patients continue to be at risk of VTE long after surgery [16]. As found in this review, BC patients who had undergone cystectomy have an elevated risk of VTE for up to three months after surgery [13].…”
Section: Discussion Of the Systematic Reviewmentioning
confidence: 86%
See 2 more Smart Citations
“…In our current review, the data from three studies that followed up the patients for three months after cystectomy revealed that VTE rates were still high; this may be due to patients having further treatment and hospitalisation [15,18,50]. According to the study by , the VTE rate peaks at 20 days after cystectomy in BC patients; however, patients continue to be at risk of VTE long after surgery [16]. As found in this review, BC patients who had undergone cystectomy have an elevated risk of VTE for up to three months after surgery [13].…”
Section: Discussion Of the Systematic Reviewmentioning
confidence: 86%
“…There are many possible explanations for the large variations in the rates of VTE observed within this group: for example, the heterogeneity of risk factors in this population that could affect the rate of VTE such as minimal invasive (robotic) cystectomy or open radical cystectomy [10]. Additionally, 33 of the included studies did not state, discuss or categorise BC patients according to confounding factors that alter the rate of VTE such as receiving surgical thromboprophylaxis for 14 or 28 days, which then makes it difficult to compare rates between studies [13,[15][16][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. All included studies, with the exception of two [19][20], did not clearly discuss or state the thromboprophylaxis measures employed.…”
Section: Discussion Of the Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many possible explanations for the large variations in the rates of VTE observed within this group: for example, the heterogeneity of risk factors in this population that could affect the rate of VTE such as minimal invasive (robotic) cystectomy or open radical cystectomy [10]. Additionally, 33 of the included studies did not state, discuss or categorise BC patients according to confounding factors that alter the rate of VTE such as receiving surgical thromboprophylaxis for 14 or 28 days, which then makes it difficult to compare rates between studies [13,[15][16][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. All included studies, with the exception of two [19][20], did not clearly discuss or state the thromboprophylaxis measures employed.…”
Section: Discussion Of the Systematic Reviewmentioning
confidence: 99%
“…In our current review, the data from three studies that followed up the patients for three months after cystectomy revealed that VTE rates were still high; this may be due to patients having further treatment and hospitalisation [ 15 , 18 , 50 ]. According to the study by Wallis et al (2017), the VTE rate peaks at 20 days after cystectomy in BC patients; however, patients continue to be at risk of VTE long after surgery [ 16 ]. As found in this review, BC patients who had undergone cystectomy have an elevated risk of VTE for up to three months after surgery [ 13 ].…”
Section: Reviewmentioning
confidence: 99%